KEMASAN IDEOLOGI DALAM PESANTREN - Lilik Ummi Kaltsum (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
The Indonesian Parliament has passed the Pesantren Law. An important point of the Pesantren Law is the state's recognition of pesantren graduates, both formal and informal. Pesantren data from the Ministry of Religion of the Republic of Indonesia is divided; 12,626 pesantren that focus on studying the Book (Yellow), and 15,109 pesantren who study the Book and other educational providers, with a total of 27,735 pesantren in Indonesia.In an Islamic boarding school, an ideological spirit will be found. The kyai will teach his chosen ideology to all students, both in attitude and speech, both in formal and informal learning. Scientific transformation as well as ideology will gradually form a santri figure similar to his kyai. And the pesantren culture continues to be rooted in obedience and loyalty between the kyai and santri. This situation led to the same spirit. This paper will photograph pesantren in packaging certain ideologies. What is the argument for choosing ideology? How do you socialize it?